Wheat in tropical environments - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Vesicular-arbuscular mycorrhiza management by Ewald Sieverding 1991 371pp lSBN 3 88085 462 9 pbk GTZ, Postfach 5180 6236 Eschborn 1, GERMANY